Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Kinerja Individu pada Usaha Kecil dan Menengah di Nusa Penida - lesmana, wahyu indra; Suaryana, I Gusti Agung (E-Jurnal Akuntansi, 2014)
The research was conducted on SMEs located in the district of Nusa Penida . The number of samples taken 30 people using purposive sampling method in particular judgment sampling . The data was collected using a questionnaire distributed to respondents . Technical analysis of the data used is a simple linear regression . Based on the analysis conducted found that the value of the regression coefficient of 0.493 which illustrates that the accounting information systems have a positive effect on the performance of individuals , meaning that the improvements in the use of accounting information systems on the performance of individual companies in the company in this case in the District of Nusa Penida SMEs will increasingly well anyway . Accounting information system to give effect to the performance of individuals in SMEs in the district of Nusa Penida was 34.5 % and the remaining 65.5 % were contributed by other variables not included in the model proposed in this study , so that the degree of influence between variables such studies are in moderate correlation
Keywords: accounting information system, individual performance